Pengaruh Media Wayang Kartun terhadap Keterampilan Menulis Cerpen Peserta Didik Kelas XI SMK Negeri 1 Kersana - Syarif Hidayatullah; Prasetyo Yuli Kurniawan; Ghufroni Ghufroni (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to identify the effect of cartoon puppet learning media on short story writing skills (short stories). Used in this study is the experimental method. The subject matter used in the research is the material for writing short stories (short stories). This study was analyzed by using the hypothesis test paired sample t test and independent sample t test. The results obtained from the paired sample t test Sig value. (2-tailed) of 0.000 < 0.05. The calculated t value is 15,783 and the t table value is 2,086. This shows that the value of t count 10,883 > t table 2,086. This means that Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the average value between the results of the pretest and the average value of the posttest results in the experimental class. This proves that there is a significant influence from the use of cartoon puppet learning media on the short story writing skills of students in class XI SMK Negeri 1 Kersana. The results obtained from the independent sample t test test the value of Sig. (2-tailed) of 0.000 < 0.05. The calculated t value is 16,900 and the t table value is 2,021. This shows that the t arithmetic value is 16.900 > t table 2.021. This means that Ho is rejected and Ha is accepted. So it can be concluded that there is a difference in the average value between the posttest results of the experimental class (using cartoon puppet media) and the average value of the control class posttest results (not using cartoon puppet media). This proves that there is a significant influence from the use of cartoon puppet learning media on the short story writing skills of students in class XI SMK Negeri 1 Kersana. Descriptively, there is a difference in the average posttest score for short story writing skills in the experimental class (using cartoon puppet media) with the average posttest score for the control class short story writing skill (not using cartoon puppet media). This is indicated by the average value of the posttest results of the experimental class which is higher than the average value of the posttest results of the control class. The average value of the control class posttest results is 65.24; while the average value of the posttest results of the experimental class is 87.86.